Relationship between crystal growth and surface/volume mobilities in Se95Te5 bulk glasses and thin films - Martinková, Simona; Valdes Mitchell, Diego Alejandro; Šlang, Stanislav; Pálka, Karel; Barták, Jaroslav (Pergamon-Elsevier Science Ltd., 2021)
The mobility of structural units in amorphous materials has a significant influence on crystal growth. In this study, we show that the motion of structural units from the amorphous matrix to the growing crystals in the volume of the Se95Te5 bulk samples can be adequately described by viscosity. Nevertheless, surface crystal growth results in a much faster growth in bulk and thin films samples, which can be attributed to a high surface mobility, similar to the behavior of organic molecular glasses. Based on current theories, the crystal growth in Se95Te5 bulk and thin film was described by standard crystal growth models, with the kinetic mobility represented in terms of viscosity and surface diffusion. Furthermore, the surface crystal growth in Se95Te5 was monitored at temperatures down to the glass transition temperature and below, and exhibited a similar behavior to that observed in molecular glasses. In addition, the near-surface viscosities estimated from the smoothing process of a periodic sinusoidal surface grating embossed onto the surface of thin film and bulk samples exhibited similar values to the bulk viscosities. (C) 2021 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Vztah mezi růstem krystalů a mobilitou na povrchu a v objemu Se95Te5 skel a tenkých filmů
Keywords: crystal growth; diffusion; viscosity; thin film; bulk amorphous materials; růst krystalů; difuze; viskozita; tenký film; amorfní materiál